2021
DOI: 10.1182/bloodadvances.2021005314
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia in patients with COVID-19: a systematic review and meta-analysis

Abstract: Heparin thromboprophylaxis is routinely administered during hospitalization for coronavirus disease 2019 (COVID-19). Due to the immune stimulation related to COVID-19, there is ongoing concern regarding a heightened incidence of heparin-induced thrombocytopenia (HIT). We performed a literature search using PubMed, EMBASE, Cochrane and, medRxiv database to identify studies that reported clinical and laboratory characteristics and/or the incidence of HIT in COVID-19 patients. The primary aim was to systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
(150 reference statements)
1
23
0
1
Order By: Relevance
“…Consequently, the 4Ts pre-test clinical scoring system for HIT is used in clinical practice to make a semiquantitative diagnosis [ 17 ]. Reported confirmed cases of HIT in COVID-19 showed intermediate or high scores, with a median of 5 points in the 4Ts score [ 6 , 18 ], as in our case, which was as high as 7 points. It is important to promptly discontinue heparin and initiate non-heparin anticoagulation therapy when HIT is suspected with a 4Ts score of 4 points or greater.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Consequently, the 4Ts pre-test clinical scoring system for HIT is used in clinical practice to make a semiquantitative diagnosis [ 17 ]. Reported confirmed cases of HIT in COVID-19 showed intermediate or high scores, with a median of 5 points in the 4Ts score [ 6 , 18 ], as in our case, which was as high as 7 points. It is important to promptly discontinue heparin and initiate non-heparin anticoagulation therapy when HIT is suspected with a 4Ts score of 4 points or greater.…”
Section: Discussionsupporting
confidence: 70%
“…Recent findings suggest that critically ill patients with COVID-19 are prone to complications with HIT [ 5 , 6 ]. A systemic review and meta-analysis on HIT in hospitalized COVID-19 patients reported that the incidence was higher in critically ill patients compared with non-critically ill patients (2.2% and 1.2%, respectively), although the incidence of 0.8% HIT in hospitalized patients with COVID-19 was comparable to that in patients without COVID-19 [ 6 ]. Clinical characteristics among the 19 confirmed cases of HIT in patients with COVID-19 in a systemic review [ 6 ] showed the following results: the median age was 62 years, and all but one patient were critically ill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that one of the main characteristics of COVID-19 is hypercoagulability, and therefore the increased risk of venous and arterial thrombosis, it is necessary to differentiate from Heparin-induced thrombocytopenia (HIT) [ 67 , 68 , 69 ], particularly secondary to the use of vaccines [ 70 ]. Uaprasert et al [ 71 ], in a systematic review and meta-analysis, found a pooled incidence of HIT of 0.8%, being slightly higher in critically ill COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%